STUDY TO RIVER PORT FACILITIES OF TOURISM PURPOSE PALANGKA RAYA - Wiratno; Samuel Layang (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2013)
This research objective is for investigates existing facilities of the River Port of Tourism Purpose, Palangka Raya according to Indonesian Article PP RI No. 61 / 2009 concerning Port. This research is arranged by main data collected from field investigation and secondary data from Dinas Perhubungan Provinsi Kalimantan Tengah (Board of Transportation Affair of The Central Kalimantan). The main stages in this research consist of data collecting and processing. Data of existing facilities are compared to required facilities by the PP RI No. 61/2009. Based on analysis result, the existing river port facilities have been not complying yet criteria of PP RI No. 61/2009 concerning Port. There were 14 of 26 requirements of the river port criteria not available or approximately more than 50% criteria uncomplying. It is important to renovate its river port facilities, especially to main facilities which connected to passenger security, safety and convenience. And the most important point to arrange are a regularly maintenance to its facilities.